2016
DOI: 10.1088/0953-2048/29/6/065022
|View full text |Cite
|
Sign up to set email alerts
|

Electrical potential distribution in terahertz-emitting rectangular mesa devices of high-Tcsuperconducting Bi2Sr2CaCu2O${}_{8+\delta }$

Abstract: Excessive Joule heating of conventional rectangular mesa devices of the high-transition-temperature superconductor Bi2Sr2CaCu2O leads to hot spots, in which the local temperature . Similar devices without hot spots are known to obey the ac-Josephson relation, emitting sub-terahertz (THz) waves at frequencies , where V is the applied dc voltage or electrostatic potential and N is the number of active junctions in the device. However, it often has been difficult to predict the emission f from the applied V … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 36 publications
0
7
0
Order By: Relevance
“…However, the introduction of a dc current I into the mesa has also led to severe Joule heating problems, resulting in the formation of inhomogeneous hot spots over which the local temperature ( ) > r T T c [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. This Joule heating also caused the restrictions V < 1.5 V, f < 1.0 THz, and µ < P 30 W from a single mesa [57][58][59][60], although a three-mesa array was reported to have a combined emission P of 0.6 mW [61].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the introduction of a dc current I into the mesa has also led to severe Joule heating problems, resulting in the formation of inhomogeneous hot spots over which the local temperature ( ) > r T T c [40][41][42][43][44][45][46][47][48][49][50][51][52][53][54][55][56]. This Joule heating also caused the restrictions V < 1.5 V, f < 1.0 THz, and µ < P 30 W from a single mesa [57][58][59][60], although a three-mesa array was reported to have a combined emission P of 0.6 mW [61].…”
Section: Introductionmentioning
confidence: 99%
“…The important question of the sample homogeneity was raised by comparing the results of thin cylindrical (disk) conventional mesa IJJ emitters and thermally-managed IJJ disk MSAs [49,55,64,70,71]. In three conventional disk mesas, the strongest emission was observed at that of the lowest frequency TM(1,1) disk mode, the wave function of which has a line node passing through the disk center at some angle.…”
Section: Introductionmentioning
confidence: 99%
“…Also, similar to the case illustrated above, 𝑉 𝑏 was found to be considerably higher than its value predicted using the emission frequency. This is believed to be due to excess voltage along the ab-plane accompanied by nucleation of hotspots [50]. as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The local temperature distributions TðrÞ of the IJJ mesa devices have been measured in detail, and the results have been discussed in comparison with theoretical studies. [14][15][16][40][41][42][43][44][45]51,[63][64][65][66][78][79][80] These studies concluded that the spontaneous formation of a local temperature instability known as a hot spot can occur in the IJJ-THz emitter device due to both the quasi-two-dimensional thermal and electrical conductivities, the latter yielding a semiconducting-like temperature dependence of the c-axis normal state resistivity for under-doped Bi2212 single crystals. Previous studies revealed that a hot spot, within which the local temperature TðrÞ > T c , acts as a shunt resistance inserted parallel to the 0021-8979/2018/124(3)/033901/9/$30.00…”
Section: Introductionmentioning
confidence: 96%